2014
DOI: 10.1200/jco.2014.55.8817
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Admissions for Cancer in the Final Days of Life: Independent Predictors and Implications for Quality Measures

Abstract: Purpose To define patient characteristics associated with hospice enrollment in the last 3 days of life, and to describe adjusted proportions of patients with late referrals among patient subgroups that could be considered patient-mix adjustment variables for this quality measure. Methods Electronic health record–based retrospective cohort study of patients with cancer admitted to 12 hospices in the Coalition of Hospices Organized to Investigate Comparative Effectiveness network. Results Of 64,264 patients adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…8 About a decade later, a study of over 64,000 patients demonstrated similar results: patients with hematologic cancers had 52% higher odds of a hospice length of stay ≤ 3 days compared to those with solid malignancies. 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 About a decade later, a study of over 64,000 patients demonstrated similar results: patients with hematologic cancers had 52% higher odds of a hospice length of stay ≤ 3 days compared to those with solid malignancies. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Short hospice stays (£3 days) have increased to 28.4% of all hospice stays 1 and 14.3% of patients with cancer who enroll in hospice do so in the last 3 days of life. 16 While lack of hospice utilization or underutilization may be attributable to documented differences in patient characteristics (e.g., diagnosis, race, ethnicity, and income [17][18][19][20][21][22], and geographic region (e.g., hospice resources available, variation in services hospices provide [23][24][25] ), the decision-making process regarding hospice enrollment is often based within the family unit. 22,[26][27][28][29] While the family has a crucial role in determining hospice utilization, little is known about how family characteristics are associated with the decision to use hospice.…”
Section: Introductionmentioning
confidence: 99%
“…The study population included patients of all ages (36% were , 65 years of age) with a wide range of insurance types, which has previously been associated with hospice lengths of stay. 32 It also included patients who recurred with advanced cancer and may have different experiences near death than patients with advanced cancer at diagnosis.…”
Section: Discussionmentioning
confidence: 99%